Pemanfaatan Aplikasi Canva sebagai Media Pembelajaran Multimedia Interaktif di Madrasah Ibtidaiyah - Alfatih, Abdullah Muhammad; Jannah, Hannatul; Raharjo, Raharjo (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2024)
Digital technology has shaped Generation Z and Alpha students in the way they interact and acquire information. However, teachers are reverting to their lecture methods and abandoning information technology (IT) when creativity is the number one skill in learning. This research offers a Canva application that aims to develop it as an interactive multimedia-based learning media. This development research uses the ADDIE model, carried out step by step. The ADDIE model used in this research starts from the Analyze, Design, Develop, Implement, and Evaluate stages to develop the Canva application as a learning product design. The results of this study revealed that media development with the Canva application obtained valid criteria from the assessment conducted by material and media experts. Canva, as an interactive learning media is very practical to use. Its practicality supports both practicality in time, place, and from the point of use. Canva media development also obtained a feasibility response from students with interesting criteria in terms of presentation feasibility, content feasibility, language feasibility, and design feasibility because each aspect of feasibility is in the percentage of 80-100%. This feasibility percentage shows that the development of Canva as a learning media is liked and interested by students and is effective for learning Fiqh.